Extraction of caprolactam in a rotating disk contactor extractor - Cato, David A. (Kansas State University, 2016)
Caprolactam (C₆H₁₁NO) is produced in industry primarily as a monomer to be converted to nylon-6 via a polymerization reaction. More demanding purity requirements for nylon-6 have increased the performance requirements of extraction columns in the purification train of caprolactam production. Caprolactam is produced by performing a Beckmann Rearrangement on cyclohexanone oxime followed by a neutralization of the excess oleum post reaction. The resulting side product is ammonium sulfate in water with a residual amount of caprolactam that has to be extracted with benzene from the aqueous ammonium sulfate solution to reduce product losses. The aqueous caprolactam liquor is extracted in another column into benzene which purifies the product from water soluble impurities. The resulting caprolactam dissolved in benzene is back extracted into water where the final purification steps are completed prior to storage. Rotating disk contactor (RDC) extraction columns were invented by Royal Dutch Shell in the early 1950’s. The columns have a rotor in the center that is driven by an electric motor to rotate equally spaced flat disks inside the column. There are equally spaced annulus shaped stators that serve to provide mixing-separation compartments for each of the mounted disks on the rotor. Of the variables to consider for the optimum performance of the extraction in the RDC extraction column is the rotor speed. Rotor speed curves are generated for the 3 RDC extraction columns of the caprolactam purification as well as calculations of the number of theoretical stages for each of the columns based on actual performance data. Benzene is the solvent of choice in this purification process however recent push by environmental groups and agencies as well as tightening regulations have driven a desire to find a more benign alternative to benzene for this process. A review of the research and literature on potential alternative solvents for caprolactam purification is summarized with positives and drawbacks for each possible alternative.
Keywords: RDC; Extraction; Caprolactam; Benzene; Rotating Disk